2019
DOI: 10.1039/c8lc00792f
|View full text |Cite
|
Sign up to set email alerts
|

An inexpensive smartphone-based device for point-of-care ovulation testing

Abstract: The ability to accurately predict ovulation at-home using low-cost point-of-care diagnostics can be of significant help for couples who prefer natural family planning. Detecting ovulation-specific hormones in urine samples and monitoring basal body temperature are the current commonly home-based methods used for ovulation detection; however, these methods, relatively, are expensive for prolonged use and the results are difficult to comprehend. Here, we report a smartphone-based point-of-care device for automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…These algorithms are easily adaptable to different imaging platforms and are not limited to expensive time-lapse imaging platforms. Previous studies on using deep-neural networks have shown their portability to inexpensive hardware such as portable computers (<$100) and smartphones (<$5) ( 12 , 22 ). The underlying costs of the technology associated with developing these networks promises easier and increased adoption of the technology from a scalability standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms are easily adaptable to different imaging platforms and are not limited to expensive time-lapse imaging platforms. Previous studies on using deep-neural networks have shown their portability to inexpensive hardware such as portable computers (<$100) and smartphones (<$5) ( 12 , 22 ). The underlying costs of the technology associated with developing these networks promises easier and increased adoption of the technology from a scalability standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In a more integrated platform equipped with a dedicated cartridge containing all necessary buffers and pre-loaded with all reagents, LH, follicle-stimulating hormone (FSH), β-hCG, and prostaglandin were simultaneously analyzed in serum using a sandwich immunoassay followed by quantitative fluorescence detection [15]. More recently, a completely different approach was proposed that used microliter-sized saliva samples dried in a microfluidic device and smartphone imaging [16]. Fern patterns resulting from sample drying were analyzed using artificial intelligence in saliva in the ovulation period, to reveal an increase in salivary electrolytes reflecting the higher estradiol level in blood.…”
Section: Portable Miniaturized Devices For Studying and Monitoring Reproductive Statusmentioning
confidence: 99%
“…Each 3D printing method has a unique set of tradeoffs in resolution, cost-efficiency, biocompatibility, and output volume, enabling the use of 3D printing in a wide range of applications ( Bakhshinejad and D'souza, 2015 ; Park et al., 2015 ). The ability to use biomaterials in 3D printing processes ( Chia and Wu, 2015 ), along with microscale and nanoscale 3D printing ( You et al., 2018 ), can enable the fabrication of a wide range of laboratory instruments for clinical and point-of-care applications ( Aimar et al., 2019 ; Amin et al., 2016b ; Douroumis, 2019 ; Knowlton et al., 2015c ; Yenilmez et al., 2016a ), including organ-on-a-chip devices ( Jain et al., 2020 ; Knowlton and Tasoglu, 2016 ; Knowlton et al., 2016b , 2016c ), tissue engineering ( Knowlton et al., 2018 ; Sears et al., 2016 ; Zhang et al., 2019 ), wound healing ( Joseph et al., 2019 ; Tabriz et al., 2020 ), fertility and embryology research ( Kanakasabapathy et al., 2019 ; Knowlton et al., 2015d ; Potluri et al., 2018 ), cancer research ( Knowlton et al., 2015a , 2016a ), stem cell research ( Javaid and Haleem, 2020 ; Tasoglu and Demirci, 2013 ), and circulating tumor cell isolation ( Chen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%